Analisis Throughput Pada Sistem Komunikasi Mobile WIMAX HAPS - Widdha Mellyssa (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
HAPS (High Altitude Platform Station) is an airship or aircraft positioned 17-22 km altitude, or in stratosphere. HAPS is the development infrastructure of telecommunication network as BTS/BS replacement. BTS / BS is seen still has shortcomings in funding and capacity range. HAPS position is on the air layer will effected by wind disgusting so that position of HAPS will change form its normal state called Platform Displacement. Therefore, in this research, we will discuss the impact of HAPS displacement on the quality of service perceived MS (Mobile Station) by measuring the throughput. Throughput values will be mesured during MS is doing handover (HO) process, user is a mobile user who is doing WiMAX VoIP communications. Users will be simulated moves with constant speed of 50 km / h, 80 km / h, 120km / h and 200 km / h. Platform will simulated in some position upward, downward, to the right and to the left. When platform moves upward, cells will increase the coverage so each cell will interfere their neighbor especially when MS is doing HO process